Photoelectrochemical water splitting process using titanium dioxide photocatalyst: A brief overview - Wei, Lai Chin; Chau, Jenny Hui Foong (Malaysian Catalysis-An International Journal, 2021)
Hydrogen (H2) has proved itself as a viable future energy carrier and alternative for fossil fuel in terms of ensuring a clean and sustainable energy supply. However, H2 must be made available at a lower cost so that everyone can benefit from it and prevent causing a worldwide ecological imbalance. The usage of photoelectrochemical water splitting (PEC) technology by using TiO2 photocatalyst can produce H2 using renewable solar energy. The essential milestones, as well as the mechanism in PEC H2 generation, are discussed in this article.